Towards information management framework for digital twin in aircraft manufacturing - Singh, Sumit; Shehab, Essam; Higgins, Nigel; Fowler, Kevin; Erkoyuncu, John Ahmet; Gadd, Peter (Elsevier, 2021)
Aircraft manufacturing industries often evolve in the ecosystem of complex designs and manufacturing processes associated with large volume of information generated along the lifecycle. Digital Twin (DT) technology has the potential of leveraging such information to provide useful insights benefiting the overall business in many ways. Information Management (IM) for DT is still an ongoing challenge for many industries, thus leaving a considerable research gap. In this paper, an IM framework for DT in the aircraft manufacturing sector is proposed. The key phases and elements of IM are discussed on which the framework is constructed. The potential application of the framework along aircraft lifecycle is further discussed. The framework not only provides an effective approach to managing information but also opens new research prospects in DT domain.
Keywords: Information Management (IM); Aircraft Manufacturing; Digital Twin (DT)